The effect of eight-weeks corrective games on kyphosis angle and postural control in mentally retarded children having kyphosis - Leila Ahmadnezhad; Ahmad Ebrahimi Atri; Nahid Khoshraftar Yazdi; Yahya Sokhangoei (Gonabad University of Medical Sciences, 2015)
The purpose of this study was to examine the effect of eight weeks corrective games on kyphosis angle and postural control in kyphotic mentally retarded children. Method: Thirty mentally retarded girls children with increase normal thoracic kyphosis (kyphosis angle≥40) were selected and randomly divided in two groups training group (N=15 with mean average 12/06±2/8 years old, Height 145±1/33cm, weight 42/33±1/38 kg) and control group (N=15 with mean average 12/26±2/8 years old, Height 144±9/8 cm, weight 43/66±1/31 kg).The angle of kyphosis measured by using flexible ruler and the Biodex Balance System (BBS) was used to evaluate static and dynamic postural control performance. The Experimental group performed corrective games a period of eight weeks (three sessions per week) and during this period control group did not experience any exercises. Independent and dependent T test used to analyze the data. All statistical analyze were performed using spss statistical software version 16 and significance level was set on 0/05. Result: The result of the research showed that corrective games was significantly positive affected on kyphosis angle and on all of the directions in static and dynamic postural control of mentally retarded children. So we can suggested the performance of corrective exercise for mentally retarded children.